Variation in Plastome Sizes Accompanied by Evolutionary History in Monogenomic Triticeae (Poaceae: Triticeae) - Chen, Ning; Sha, Li-Na; Wang, Yi-Ling; Yin, Ling-Juan; Zhang, Yue; Wang, Yi; Wu, Dan-Dan; Kang, Hou-Yang; Zhang, Hai-Qin; Zhou, Yong-Hong; Sun, Gen-Lou; Fan, Xing (Frontiers in Plant Science, 2021)
To investigate the pattern of chloroplast genome variation in Triticeae, we comprehensively analyzed the indels in protein-coding genes and intergenic sequence, gene loss/pseudonization, intron variation, expansion/contraction in inverted repeat regions, and the relationship between sequence characteristics and chloroplast genome size in 34 monogenomic Triticeae plants. Ancestral genome reconstruction suggests that major length variations occurred in four-stem branches of monogenomic Triticeae followed by independent changes in each genus. It was shown that the chloroplast genome sizes of monogenomic Triticeae were highly variable. The chloroplast genome of Pseudoroegneria, Dasypyrum, Lophopyrum, Thinopyrum, Eremopyrum, Agropyron, Australopyrum, and Henradia in Triticeae had evolved toward size reduction largely because of pseudogenes elimination events and length deletion fragments in intergenic. The Aegilops/Triticum complex, Taeniatherum, Secale, Crithopsis, Herteranthelium, and Hordeum in Triticeae had a larger chloroplast genome size. The large size variation in major lineages and their subclades are most likely consequences of adaptive processes since these variations were significantly correlated with divergence time and historical climatic changes. We also found that several intergenic regions, such as petN–trnC and psbE–petL containing unique genetic information, which can be used as important tools to identify the maternal relationship among Triticeae species. Our results contribute to the novel knowledge of plastid genome evolution in Triticeae.